Analyzing the Characteristics of Fishbone Powder Derived from Pangasius sp., Thunnus tonggol, and Thunnus albacares as Food Fortificant - Novianty, Hilda; Sefrienda, Ardiba Rakhmi Sefrienda Rakhmi; Jasmadi, Jasmadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Pangasius sp., Thunnus tonggol (T. tonggol), and Thunnus albacares (T. albacares) are high-value commercial species widely used in fillet production, generating by-products, such as fishbone. The fishbone, rich in calcium (CA) and phosphorus (P), offers a valuable alternative for daily Ca intake. Using such by-products as a potential source of Ca presents a viable solution, offering food-fortificant ingredients applicable in various food products. Therefore, this study examined the physical and chemical properties of fishbone powder derived from Pangasius sp., T. tonggol, and T. albacares. The products preparations were subjected to cooking, autoclaving, pulverization, homogenization, drying, and grinding. The physical and chemical analysis of fishbone powder showed that T. tonggol and T. albacares had a darker color compared to Pangasius sp., with higher protein content and likely stimulation of a Maillard reaction during the drying process. All species maintained a neutral pH range, and their particle sizes significantly differed (p< 0.05), ranging from nm to µm. SEM images showed irregularly shaped and agglomerated particles in all fish species. The ash content was 54.35 g/100 g (Pangasius sp.), 53.62 g/100 g (T. tonggol), and 52.28 g/100 g (T. albacares), showing high mineral content, particularly in Ca exceeding 40%. The analysis of a Fourier transform infrared spectroscopy (FT-IR) showed carbonate and phosphate peaks, representing the presence of calcium salts. Based on the evaluation, fishbone powder for each species had the potential to serve as food fortificant.